2009
DOI: 10.1111/j.1439-0396.2008.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starch gelatinisation on nutrient digestibility and plasma metabolites in pigeons

Abstract: Feed manufacturing exerts physical and chemical changes in ingredients, including the gelatinisation of starch. Studies on the effect of the degree of starch gelatinisation on nutrient digestibility, metabolism and subsequent performance show inconsistent results, and no data are available in pigeons. In a cross-over trial, fourteen adult pigeons were randomly divided into two groups, in which two extruded pellet diets were tested. Both the diets were similar in ingredient composition and nutrient content, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…Body weight increase tended to be higher with low starch gelatinisation degree in time, despite similar feed intake. Comparable results were found in our previous study (Abd El‐Khalek et al., 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Body weight increase tended to be higher with low starch gelatinisation degree in time, despite similar feed intake. Comparable results were found in our previous study (Abd El‐Khalek et al., 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The reduction in the pH in crop and gizzard through mild starch gelatinisation supports earlier findings that lower starch gelatinisation degree enhances nutrient digestibility in pigeons (Abd El‐Khalek et al., 2009). The mechanism involved might be similar to the use of carbohydrase enzymes: Jozefiak et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, crude ash digestibility-as a measure of mineral absorption-showed a considerable increase due to decreasing the degree of starch gelatinisation of a complete extruded diet for pigeons [18]. A consecutive trial indicated that intestinal pH and changes in intestinal morphology might attribute to this phenomenon [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on African grey parrots (Psittacus erithacus), raw material particle size did not change nutrient digestibility, but coarse ground feed promoted firmer stools (Kalmar et al, 2007). For pigeons, starch cooking reduced protein and fat digestibility and promoted moist excreta formation (Abd El-Khalek, Kalmar, Van Weyenberg, Werquin, & Janssens, 2009). In a study comparing extruded versus pelleted diets for macaws, the intake of less gelatinized starch in the pelleted diets resulted in reduced glucose, cholesterol and triglyceride concentrations in the plasma (Veloso et al, 2014), a parameter related with some chronic disease of parrots, such as liver diseases and atherosclerosis (Bavelaar & Beynen, 2004), although the pathogenesis of these diseases in parrots is little studied and serum markers are not validated yet.…”
Section: Introductionmentioning
confidence: 99%